The "Other" in Kurdish Novel (Derave Tang) as an example - Saeed, Zozan S. (Academic Journal of Nawroz University, 2018)
The" other", in the simplest forms, is the opposite of the "self" or ego. There is no doubt that what the world is witnessing today of political tension and sectarian and racial conflicts have affected the "self" that is often in conflict with the "other’ since they are different intellectually, religiously, culturally and sexually. The novel is one of the literary genres which reflects the "self " and the "other’ on all levels. The other in Kurdish literature (narrow times) is a model has often been associated with the governments that tried to erase all traces of Kurdish culture and heritage. Hence the other in the Kurdish novel has often been perceived as a greedy colonial who tried to control the land and fortunes of the Kurdish people.